Stakeholder perspectives on blockchain technology adoption for public governance in Nigeria - a qualitative study - Oni, Oluwasola (Edelweiss Applied Science and Technology, 2024)
The purpose of this paper is to investigate the perspectives and expectations of the stakeholders involved in this diffusion process, with the objective of assessing Nigeria's position along the innovation diffusion process. Although a national policy for the adoption of the technology has been published recently. There is very scant literature on the “perspectives of key stakeholders” on blockchain adoption. This paper attempts to address that gap by gathering insights through the views of various stakeholders involved in the innovation-decision process, including public officials, vendors, end users, and consultants, with the aid of interviews. With an initial exploratory study using the theoretical frameworks of Social Construction of Technology (SCOT) and Innovation Diffusion Theory, results reveal that the adoption of blockchain technology for governance is at the decision phase. Private developers exhibit enthusiasm and preparedness for blockchain integration, as against mild reservations within governmental bodies and financial institutions, primarily concerning security, scalability, and regulatory frameworks. The paper suggests that future research endeavours to embrace complementary methodologies and cross-sectoral analyses, to identify sector-specific challenges in the adoption of blockchain technology